Expert system techniques in biomedical science practice - Pattnaik, Prasant Kumar 1969-; Swetapadma, Aleena 1983-; Sarraf, Jay 1989- (IGI Global, Disseminator of Knowledge, 2018)
"This book explores the strategic role of expert system techniques in biomedical science practice. It covers topics such as biomedical signal and image processing, artificial intelligence, biomedical Learning, control systems, and the implementation of soft computing techniques in biomedical engineering" - Provided by publisher
Includes bibliographical references
Keywords: Expert Systems; Medical Informatics Applications